Foreign direct investment and income inequality in transitional economies: Array - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2020)
The study investigated the impact of FDI on income inequality and using technology to avoid omitted variable bias. Fixed effects, random effects and pooled ordinary least squares were used with data spanning from 2005 to 2015. Although the subject on FDI and its absorption capacities have been going on for almost a decade now, there is no consensus yet on the list of factors that enables FDI to influence income inequality. Wu and Hsu (2012) and Mihaylova (2015) attempted to investigate to investigate FDI-inequality-absorption capacities but the findings are not clear with regards to ICT as an absorption capacity. The current study found out that the interaction between ICT and FDI had a non-significant positive influence on income inequality in transitional economies. The study urges the transitional economies to develop ICT policies that enhances FDI’s ability to reduce income inequality.